Women in Numbers Europe: Research Directions in Number Theory - Bertin, Marie J.; Bucur, Alina; Feigon, Brooke; Schneps, Leila (Association for Women in Mathematics Series, 2015)
Explicit construction of Ramanujan bigraphs -- Classifications of Elliptic Fibrations of K3 surfaces -- Classifications of Elliptic Functions of a singular K3 Surface -- Shalika Germs for Sl(n) and Sp(2n) are Motivic -- The Conjectural Relation Between Generalized Shalika Models on SO4n(F) and Symplectic Linear Models on Sp4n(F): A Toy Example -- Bad Reduction of Genus Three Curves with Complex Multiplication -- Symmetries of Rational Functions Arising in Ecalle's Study of Multiple Zeta Values -- On T-Li Coefficients for Rankin-Selberg L-Functions -- Galois Representations and Galois Groups over Q